1997
DOI: 10.1042/bj3260539
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein is strongly expressed in the luminal membranes of the endothelium of blood vessels in the brain

Abstract: Luminal membranes of the vascular endothelium were isolated from brain, heart and lungs by modification of their density. The presence of P-glycoprotein (P-gp) was detected by Western blotting in luminal membranes from the endothelium of the three tissues. Strong enrichment in brain capillary luminal membranes, compared with brain capillaries (17-fold) and whole membranes (400-500-fold), indicates that P-gp is mainly located on the luminal side of the brain endothelium. Western blotting was also performed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
164
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(171 citation statements)
references
References 29 publications
6
164
1
Order By: Relevance
“…Luminal P-gp expression has been observed in isolated human brain capillaries (Seetharaman et al, 1998), human tissue (Virgintino et al, 2002), and isolated capillaries from rats (Beaulieu et al, 1997;Miller et al, 2000). The differing results of Bendayan et al to those of others in the field, including the present study, might relate to the method of fixation.…”
Section: Accepted M Manuscriptcontrasting
confidence: 60%
See 1 more Smart Citation
“…Luminal P-gp expression has been observed in isolated human brain capillaries (Seetharaman et al, 1998), human tissue (Virgintino et al, 2002), and isolated capillaries from rats (Beaulieu et al, 1997;Miller et al, 2000). The differing results of Bendayan et al to those of others in the field, including the present study, might relate to the method of fixation.…”
Section: Accepted M Manuscriptcontrasting
confidence: 60%
“…cultures of both primary and immortalised cells of rat, mouse and human origin (Beaulieu et al, 1997;Begley et al, 1996;Miller et al, 2000;Perriere et al, 2007;Seetharaman et al, 1998;Tatsuta et al, 1992;Virgintino et al, 2002). In terms of Pgp expression, the BEC phenotype appears to be preserved in hCMEC/D3 cells over a wide range of passages, and P-gp expression was comparable to cultured primary BECs, albeit slightly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting this role for Pgp includes: (1) observations of Pgp-dependent efflux of Ab in vitro, 59,60 (2) an inverse correlation of Ab deposition and microvascular Pgp expression in human brain tissue, 61 (3) decreased Ab efflux and enhanced Ab deposition in mice that lack Pgp, 62 (4) impaired microvascular Pgp function in a transgenic AD mouse model that is restored by pharmacologic intervention shows corresponding improvement in Ab efflux and reduced Ab deposition, 62,63 and (5) showing Pgp dysfunction in human AD using clinical PET imaging studies. 64 Because of its luminal location, 65 it has been proposed that Pgp facilitates the extrusion of Ab from the endothelial cell into the bloodstream after Ab has been internalized from brain interstitial fluid (ISF) by LRP-1. 63 However, our group has found that under inflammatory conditions, antioxidant treatment that preserves LRP-1 but not Pgp function also preserves Ab efflux.…”
Section: Defects In Blood-brain Barrier Transporters That May Contribmentioning
confidence: 99%
“…Indeed, overexpression of the drug efflux pump P-glycoprotein (Pgp) at endothelial cells of the brain capillaries at the blood-brain barrier (BBB) and of the newly formed capillaries around the brain tumours represents one of the key explanations for the low bioavailability of anticancer drugs that are substrates of Pgp in tumour cells. 2,3 However, it remains to be determined whether tumour cells themselves can express drug efflux pumps such as Pgp. Pgp, which is encoded by the human MDR1 gene, is a well-known drug efflux pump whose overexpression has been mainly observed in human cancer being resistant to anticancer chemotherapy.…”
mentioning
confidence: 99%